Input linearization of nonlinear systems via pulse width control - (:unkn) unknown (IEEE, Piscataway, NJ, United States, 1997)
Input linearization of a general kind of nonlinear system can be achieved by adding a pulse width (modulated) control block prior to the nonlinear system. Therefore the combined system from the pulse width control input to the nonlinear system output behaves as a linear in control system. By this way a complex and cumbersome nonlinear system model can be easily transformed to a much simpler linear in control form.